Influence of intercropping systems and sulphur on yield and quality of castor (Ricinus communis L.) in eastern Uttar Pradesh: INFLUENCE OF INTERCROPPING SYSTEMS AND SULPHUR ON CASTOR IN EASTERN UTTAR PRADESH - Y K GHILOTIA; R N MEENA; ASHVIN KUMAR MEENA; Y V SINGH; SUNIL KUMAR (Journal of Oilseeds Research, 2019)
A field experiment was conducted during kharif 2012 and 2013 at BHU, Varanasi, Uttar Pradesh to study the growth, yield and quality parameters influenced by different sulphur levels and intercropping systems. The soil of the experimental field was loamy sand having pH 7.35, organic carbon (0.37%), available nitrogen (205 kg N/ha), phosphorus (25 kg P2O5 /ha) and potash (216 kg K2O/ha). The treatments consisted of five intercropping systems [castor + mungbean (1:1), castor + mungbean (1:2), castor + mungbean (1:3), castor + mungbean (2:2 paired row) and castor + mungbean (2:3 paired row)] and four levels of sulphur (0, 20, 40 and 60 kg S/ha) were taken in strip plot design with three replications. Intercropping system (castor + mungbean, 1:1 ratio) resulted in taller plants which was at par with castor + mungbean (1:2) ratio. Application of sulphur @ 60 and 40 kg/ha produced statistically similar plant height, but significantly higher than application of sulphur @ 0 and 20 kg/ha. Dry weight of castor was higher in castor + mungbean (1:1 and 1:2 ratios) than castor + mungbean (2:2 and 2:3 ratios) of castor and mungbean crops. The highest dry matter accumulation was recorded with the application of 60 kg S/ha which was at par with 40 kg S/ha, while dry matter accumulation was lowest with no S application. During the year 2013, significantly higher seed yield (1428 kg/ha), stalk yield (2548 kg/ha) and biological yield (3977 kg/ha) ofmungbean was recorded in castor + mungbean (1:1) intercropping and gradually reduced with increase in row proportion. Similar trend was followed in year 2012. The highest grain, stalk and biological yields of castor and mungbean were recorded with application of 60 kg S/ha (1045, 1740, 2786 and 1364, 2408, 3771 during 2012 and 2013 respectively) which was statistically similar with S40 during both years of study. Higher carbohydrate per cent, protein yield and protein per cent were recorded with castor + mungbean (1:1) which was statistically similar with castor + mungbean (1:2) during both the years of study.